SOSIALISASI PEMBUATAN ABON DARI IKAN NILA SEBAGAI PELUANG USAHA DAN PEMBERDAYAAN MASYARAKAT - Gatot Triono Senoaji; Marisa, Dea; Maharani, Citra Putri; Fiutri, Rara Astiagina; Hijriyanti, Risa; Zhalilah, Taqiyyah; Asian, Kia Putri; Irmadurisa, Ade; Haizar, Maulana Rifki; Hadi, Lalu Muh. Arifan; Elmiana, Dewi Satria (Universitas Mataram, 2025)
Community empowerment through the use of local resources, especially in Sigerongan Village, is one of the efforts to improve the welfare of economists in the village. One potential that can be developed is making shredded tilapia fish as a processed product with high selling value. This outreach activity aims to provide knowledge and skills to the community regarding the process of making tilapia floss as a potential business opportunity. The methods used in this activity include counseling, training in making shredded meat, and interactive discussions with participants. The results of this activity show that the community has high enthusiasm in learning techniques for processing tilapia into shredded fish. Apart from that, the use of tilapia as raw material for floss can increase the added value of fishery products and open up new business opportunities for local communities. With this outreach, it is hoped that the community can develop independent fisheries-based businesses and improve economic welfare through diversification of processed tilapia fish products.